Features of induction heating of cylindrical parts conjugated with an axis - V. I. Dudin; S. A. Lelekhov; A. N. Feshchukov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. This article examines the temperature of separation of a cylindrical part from the axis and its dependence on the interference and induction heating power based on theoretical calculations and experiments.Materials and methods. The calculations show the temperature of the outer surface of a cylindrical part, where the interference vanish and the part comes off without force. The authors numerically solved the heat conduction and deformation equations and determined these separation temperatures. The researchers also calculated the temperature profile over the cross-section of a cylindrical part.Results. The authors identified the dependence of the separation temperature of a cylindrical part (the inner ring of a bearing) on the power of the induction heater. The article considers the dependence of the thermal diffusivity coefficient on temperature and examined the features of fitting cylindrical parts on axes and shafts.Discussion and conclusion. The research shows that the dependence of the separation temperature of a cylindrical part (the inner ring of a bearing) on power has two regions: the separation temperature is almost constant for relatively small values (up to 5-6 kW); and the separation temperature is proportional to the power for higher values, above 6 kW. In this case, the induction heater requires a controller for induction heating power and heating time. This would technically prohibit operations with parameters outside the test procedure. The research results are applicable to a wide range of axis associated parts, for example, for bands of cold pipe drawing mills, bands for the centres of locomotive wheel pairs.